(untitled) (Konturen, 2010)
Ludwig Wittgenstein’s thinking about musical aesthetics (a small but persistent strain in his writings) focused primarily on questions of demonstration and proper performance: how should this waltz or march sound? These emphases were part of a modernist-inspired effort to move aesthetics down from the heights of Kantian contemplation onto the plain of quotidian practice. But Wittgenstein does not so much escape Kant’s formulations as he extends them. The result opens the possibility of elaborating ordinary, even banal, comments about music into complex accounts of musical meaning.